Assessing the Use of Rice Husks and Spent Grain for the Removal of Heavy Metals From Surface Water - Jeremiah Richard Kayongo (Uganda Christian University, 2025)
This study assessed the use of rice husks and brewer’s spent grain as adsorbents for removing heavy metals from River Nyamwamba's water. The research aimed to address the significant heavy metal contamination in the river, posing risks for domestic use. The study employed in-situ measurements of physico-chemical properties and heavy metal analysis, followed by laboratory experiments to determine the adsorption efficiency of the biochars of rice husks and brewers’ spent grain. The findings revealed that a mix ratio of 1:3 (rice husks to brewer’s spent grain) provided the most efficient removal of copper and iron, with removal efficiencies of 95.63% and 94.63%, respectively. The study concluded that steam activation significantly enhanced the adsorbents' performance, making them effective for improving water quality. These results highlight the potential of using agricultural by-products as sustainable and cost-effective solutions for water treatment in regions affected by heavy metal pollution.
Undergraduate research